(untitled) (Bangladesh Journal of Agricultural Research, 2013)
Using line x tester mating design with three CMS lines and seven elite testers, the general combining ability (GCA) of parents and specific combining ability (SCA) of crosses were carried out for grain yield and its attributes. The SCA variance was greater than the GCA variance for grain yield and yield components, suggesting the preponderance of dominance and epistatic gene action in expression of these traits. The line CRMS 31 A and IR 79156 A were recorded as good combiners for head rice recovery percent. The tester NPT 80-1 was good general combiner for grain yield per plant and TOX 981-11-2-3 for both grain yield per plant and head rice recovery percent. The cross combinations APMS 6 A/ET 1-13, CRMS 31 A/ET 1-12, and IR 79156 A/ NP T 80-1 were found to be outstanding with respect to grain yield per plant, head rice recovery percent, and spikelets per panicle. The cross APMS 6 A/NPT 2-2-694- 1 was good combiner for head rice recovery percent. These promising lines, testers, and crosses revealed wide scope for enhancing the grain yield in the CMS line or three line breeding system based rice improvement programme to develop rice hybrids. DOI: http://dx.doi.org/10.3329/bjar.v37i4.14376 Bangladesh J. Agril. Res. 37(4): 583-592, December 2012